2022
DOI: 10.1021/acs.langmuir.2c02306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticle Addition on Evaporation of Jet Fuel Liquid Films and Nanoparticle Deposition Patterns during Evaporation

Abstract: Jet fuel-based nanofluid fuel has been proposed for improving the energy density and utilization efficiency of jet fuel that is widely applied in aircraft powered by aviation turbine engines. To recognize the evaporation behavior of the formed liquid film as a jet fuel-based nanofluid sprayed onto the engine wall or blades, this paper presents the evaporation and deposition characteristics of the jet fuel-based nanofluid liquid film adhering on the hydrophilic substrate. The changes in contact line, contact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…36 It was shown that insoluble surfactants do not produce Marangoni vortices, 37 but soluble surfactants can drive considerable recirculation. 38 Considering that Marangoni eddies can lead to unexpected distributions of solute particles 39 and have a tremendous impact on the deposition, 40 this contribution benefits from the results of the previous research done by our group. Inanlu et al 15 determined an optimum surfactant concentration in which CNTs are well dispersed in the aqueous phase and the surfactant-induced Marangoni flow has the lowest impact on the deposition, so the densest ring would be achievable.…”
Section: Introductionmentioning
confidence: 99%
“…36 It was shown that insoluble surfactants do not produce Marangoni vortices, 37 but soluble surfactants can drive considerable recirculation. 38 Considering that Marangoni eddies can lead to unexpected distributions of solute particles 39 and have a tremendous impact on the deposition, 40 this contribution benefits from the results of the previous research done by our group. Inanlu et al 15 determined an optimum surfactant concentration in which CNTs are well dispersed in the aqueous phase and the surfactant-induced Marangoni flow has the lowest impact on the deposition, so the densest ring would be achievable.…”
Section: Introductionmentioning
confidence: 99%
“…Among aviation fuels, JP-10 (C 10 H 16 , exotetrahydrodicyclopentadiene) has been widely used in aircraft with aero turbine engines [15,16], with a volumetric heat of 39.6 MJ/L, a freezing point of <−100 • C, and kinematic viscosity of 19 cSt at −40 • C [17,18]. Energetic Al nanoparticles are a type of metal fuel that has been applied in propellants as an additive due to its characteristics of a higher energy density and a low price [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Past experimental and theoretical research studies have made substantial progress in colloidal systems, liquid crystals, , and other suspensions. However, for widely used polymer solutions, the well-established framework in suspended particle droplets needs careful reconsideration. One significant distinction is that the physical properties of a polymer solution are highly dependent on the molecular weight.…”
Section: Introductionmentioning
confidence: 99%